2017
DOI: 10.1007/s12035-017-0509-3
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-8 Inhibition Prevents Disruption of Blood–Spinal Cord Barrier and Attenuates Inflammation in Rat Model of Spinal Cord Injury

Abstract: After spinal cord injury (SCI), tight junction (TJ) protein degradation increases permeability and disrupts the blood-spinal cord barrier (BSCB). The BSCB is primarily formed of endothelial cell, which forms a specialized tight seal due to the presence of TJs. BSCB disruption after SCI allows neutrophil infiltration. Matrix metalloproteinase (MMP)-8 is believed to be mainly expressed by neutrophils and is quickly released upon neutrophil activation. Here, we determined whether MMP-8 is involved in the TJ prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 65 publications
2
38
0
1
Order By: Relevance
“…The results of the analysis are presented as the mean percent of the detected levels of individual factors vs intact LE rats and analyzed with two way ANOVA (Fig 6). (1,2), intact LES rat (3,4) and post-SCI rat spinal cord at 2 (5,6), 7 (7,8), 28 (9,10) and 112 days (11,12). Arrowheads indicate the areas of injury that are GFAP -, asterix indicates a COI, 1indicates an area of arachnoiditis.…”
Section: Proteomic Analysis Of the Spinal Cord Tissue Post-scimentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the analysis are presented as the mean percent of the detected levels of individual factors vs intact LE rats and analyzed with two way ANOVA (Fig 6). (1,2), intact LES rat (3,4) and post-SCI rat spinal cord at 2 (5,6), 7 (7,8), 28 (9,10) and 112 days (11,12). Arrowheads indicate the areas of injury that are GFAP -, asterix indicates a COI, 1indicates an area of arachnoiditis.…”
Section: Proteomic Analysis Of the Spinal Cord Tissue Post-scimentioning
confidence: 99%
“…SCI initiates hemorrhage and ischemia, free radical release, severe inflammation, and cellular necrosis [5][6][7]. Pro-inflammatory cytokines such as interleukins 1beta (IL1beta) and 6 (IL-6) as well as tumor necrosis factor alpha (TNF-alpha) and interferon gamma (IFN-gamma) [7][8][9], CC, CXC and CX3C chemokines [10] and matrix metalloproteinase 8 [11] are reported to be elevated after SCI, actively promoting severe inflammation. In a recent systematic study up to 8 weeks post-SCI, plasma levels of VEGF, leptin, IP10, IL18, GCSF, and fractalkine were measured and their changing levels reported [12] but the relevance of these changes to the pathogenesis of SCI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…After flattening of the spine, a 35 g stainless steel impounder was gently placed on the dorsal surface of the spinal cord through a micromanipulator. A moderate compressive damage is delivered to the bar to deliver a 5-min waiting load ( Kumar et al, 2017 ; Figure 1B ). Following the compression injury, muscle and skin incisions were closed using appropriate monofilament sutures (Silk 4-0).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have indicated that inflammatory response and oxidative stress are two major events of the secondary injury and play contributed roles in complex secondary pathogenesis [6,58,59]. During the secondary injury cascade, the infiltrations of inflammatory cells such as macrophages, microglia and neutrophils [60,61] trigger the release of pro-inflammatory cytokines including TNF-α, IL-1β and IL-6 [62][63][64], leading to cellular necrosis or apoptosis [65]. In addition, inflammatory cells also release excess reactive oxygen species and reactive nitrogen species [66,67], which causes DNA oxidative damage, proteins oxidation and lipid peroxidation [68].…”
Section: Discussionmentioning
confidence: 99%